Celler til salg: Kunstneriske fortolkninger af vævsøkonomier - Leth-Espensen, Pernille (K&K - Kultur og Klasse, 2017)
An extensive circulation of human tissue is taking place in our society today: blood, organs, reproductive tissue (eggs and semen), and cell lines. This circulation and commercialisation is thematised by a range of contemporary artists, who create artworks with cell and tissue culture technologies. The artist Alicia King has bought Hs 53.T cells from the cell bank ATCC (The American Type Culture Collection) and created a monument around this cell line. These cells originate from a 13-year old Afro-American girl, and the cell sample was taken in 1969. The artist Chrissy Conant uses her own tissue. She has ’harvested’ 12 of her own eggs at a fertility clinic, preserved them in glass jars with a lid inspired by caviar packaging, and put them for sale at 250.000. In the article it is argued that the artworks address the commercialisation of human tissue by pointing out or make visible technologies or processes that are unknown to the broader public or which have become naturalised – rather than by having a specific political agenda. King thematises the commodification of human tissue by moving the cells from the anonymity of the cell bank, while Conant addresses the increasing commodification of reproductive tissue by literally packaging and branding her own bodily tissue as a luxury product.